Experiências lexicológicas em sala de aula: construindo glossários com alunos do ensino fundamental - SILVA, João Batista Poça da (Universidade Federal do Pará, 2018)
The lexical sciences are branches of Linguistics whose contributions are explored shortly on learners’ activities at Elementary School. Based on this assumption, we ensure that the acts of conceptualizing and defining, embodied through the discursive genre, are able to increase the students’ communicative capacity and contribute to the improvement of reading and writing. These acts, however, find a short field at the classroom, whereas the dictionary, the encyclopedia and the glossary, when used, have their interdisciplinary reach almost non-existent, because the user is usually considered a mere consultant. That is, as one who only consults publications oriented to the entry, while the ability to conceptualize (cut reality culturally and linguistically) is not appreciated. Thus, we can ask how the study of lexical aspects of language can contribute to the student’s better organization and control of the concepts studied in different curricular disciplines. This leads us to the general purpose of this work, which is to formulate, propose, apply and evaluate practices related to working with the common and specialized lexicon at the classroom, in an interdisciplinary perspective. Other purposes derive from this main one, among them: describe and analyze how textbooks of some disciplines approach the entry; mediate students’ familiarity with the different lexicographic genres; enable students to develop entries and glossaries; elaborate a didactic material proposal guided by the elaboration of entry as a resource for the reflective practice of conceptualization. The main hypotheses tested by the research postulate that the acts of conceptualizing, defining and recording in writing help student to organize ideas and improve his/her performance in different disciplines. Moreover, the relevance given to the lexical aspect of the language is minimal or non-existent in the educational and material spaces; the different lexicographic genres are underutilized as a source of deepening of contents; the lexicon is a large resource of interdisciplinary approach; the entry is a discursive genre appropriate to mediate activities on the lexicon, grammar and textual-discursive aspects; and concept and definition, properly differentiated, contribute to the student better establishment of study strategies. The theoretical contribution of this research is based on the studies of Biderman (2001), on the sciences of the lexicon; Barbosa (2001) and Finnato (2002) on conceptualization and definition; Pontes (2009), Carvalho and Bagno (2011) and Ilari (2015), on Lexicography and its theoretical, practical, pedagogic and educational subfields; Antunes (2012), on lexicon and discourse in the context of teaching-learning; Barros (2004) and Lima (2010), on Terminology and Terminography; and Dionisio (2010), on the discursive genre entry. In the methodological course, we chose the participant’s research to intermediate the observation of the task about the lexicon in a class of sixth grade at Elementary School, in four disciplines, namely, History, Sciences, Mathematics and Portuguese Language. Two sources generated data that underwent qualitative analysis: textbooks used in classes of those respective disciplines and semi structured questionnaires applied to the teachers and students of the chosen class. From the analyses, reflections and collations carried out, we elaborated and applied a proposal of intervention, and accomplishing activities of conceptualization and, consequently, the students produced glossaries. The study and application of this proposal led us to realize that activities with concepts and definitions mediated by the genre entry are an important resource for the organization and expression of knowledge and its positive results achieve several curricular subjects. We could also verify that the range of creative possibilities provides a pleasant and productive approach of the lexicon at the classroom. The result of this work is a book of didactic-pedagogical activities made available to schools.